Effects of Autonomous Sensory Meridian Response on the Functional Connectivity as Measured by Functional Magnetic Resonance Imaging - Lee, Seonjin; Kim, Jooyeon; Tak, Sungho (Frontiers in Behavioral Neuroscience, 2020)
Autonomous sensory meridian response (ASMR) is a sensory phenomenon in which audio-visual stimuli evoke a tingling sensation and is accompanied by a feeling of calm and relaxation. Therefore, there has been an increasing interest in using stimuli that elicit ASMR in cognitive and clinical neuroscience studies. However, neurophysiological basis of sensory-emotional experiences evoked by ASMR remain largely unexplored. In this study, we investigated how functional connectivity is changed while watching ASMR video, compared to resting state, and assessed its potential association with affective state induced by ASMR. 28 subjects participated in fMRI experiment consisting of 2 sessions (resting-state and task of viewing ASMR-eliciting video). Using a seed-based correlation analysis, we found that functional connections between the posterior cingulate cortex, and superior/middle temporal gyri, cuneus, and lingual gyrus were significantly increased during ASMR compared to resting state. In addition, we found that with the pregenual anterior cingulate cortex seed region, functional connectivity of the medial prefrontal cortex was increased during ASMR condition, relative to resting state. These results imply that ASMR can be elicited and maintained by ongoing interaction between regional activity that are mainly involved in the mentalizing and self-referential processing. We also found that ASMR-induced affective state changes (high/low activation negative and high activation positive state) were negatively correlated with functional connectivity involved in visual information processing, suggesting that visual information processing in response to unpleasant and high arousal states can be weakened by ASMR-eliciting stimuli.